TARGET ANALYSIS AND DEVELOPMENT ACHIEVEMENTS HEALTHY TOURISM IN REALIZING SUSTAINABLE DEVELOPMENT IN BANYUWANGI DISTRICT - Nur Anim Jauhariyah; Ahmad Munib Syafa’at; Sofi Faiqotul Hikmah; Lilit Biati; Aula Izatul Aini (FORPIM PTKIS ZONA TAPAL KUDA, 2022)
ABSTRACTTargets and achievements of healthy tourism development are an evaluation of government policies in maintaining the function of public goods as an effort to realize sustainable development. This study aims to analyze the targets and achievements of the development of tourism areas in Banyuwangi Regency in accordance with macro healthy tourism indicators and in tourist destinations with the highest number of tourist visits. The sampling technique in this study used a purposive sampling method, then a sample of 12 research respondents was obtained, namely from Bappeda, Health Office, Culture and Tourism Office, and Tourism Awareness Groups in 10 tourist destinations with the highest number of visits in 2020. The analysis used descriptive statistical analysis. about the targets and achievements of the implementation of the Healthy Regency indicators in Banyuwangi Regency. The results showed that at a macro level, Healthy Tourism Development in Banyuwangi Regency had reached the target as a Regency that deserves to be categorized as healthy tourism by 82.5%, while in the top ten tourist destinations it shows that there are still tourist destinations that have scores below 80%.Keywords: Development, healthy tourism, Banyuwangi Regency